2022
DOI: 10.1016/j.landurbplan.2021.104288
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood, built environment and children’s outdoor play spaces in urban Ghana: Review of policies and challenges

Abstract: Although a great deal of research work has been done by social scientists on walkability and playability, the focus to a large extent has been on the global north. Research work on the urban built environment and children’s play has not engaged Africa in general and Ghana in particular. More importantly, there is limited evidence of policies in terms of community-based practices and governmental policies and programmes for the promotion of play. The limited effort in promoting physical activities have to a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 74 publications
(76 reference statements)
1
8
0
Order By: Relevance
“…Additionally, studies in Pakistan and Taiwan have observed a higher rate HBV infection among males compared with females (26,27). In Ghana and sub-Saharan Africa where most infections are acquired at younger ages through horizontal transmission dynamics, this result would be expected as culturally boys rather girls would regularly be involved in more vigorous outdoor activities and are, therefore, more likely to get infected (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies in Pakistan and Taiwan have observed a higher rate HBV infection among males compared with females (26,27). In Ghana and sub-Saharan Africa where most infections are acquired at younger ages through horizontal transmission dynamics, this result would be expected as culturally boys rather girls would regularly be involved in more vigorous outdoor activities and are, therefore, more likely to get infected (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of focus and inclusion of children in built environment policy documents is not limited to Australia, with other high‐ and low‐middle income countries reporting similar findings. A recent review in Ghana highlights the lack of public policies on children's outdoor play, emphasizing a need for policies to consider children's play when designing urban built environments 75 . Similarly, a review of Irish local government policies found few policies supported the planning and improvement of the built environment for children with children's interests not adequately considered in policy and decision making 76 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent review in Ghana highlights the lack of public policies on children's outdoor play, emphasizing a need for policies to consider children's play when designing urban built environments. 75 Similarly, a review of Irish local government policies found few policies supported the planning and improvement of the built environment for children with children's interests not adequately considered in policy and decision making. 76 It was recommended more should be done to increase the visibility of children when planning policy.…”
Section: Discussionmentioning
confidence: 99%
“…Every area of child development has the potential to improve a child's education, social life, and general welfare [30], basically children's basic movement patterns can develop naturally, and a higher level of child proficiency is achieved with proper practice, encouragement, and instruction, children who cannot receive instructions properly will show delays in the development of motor competence [8] which have an impact on emotional and social functioning [31]. Playing can develop movement skills, social, thinking and behavior as well as the emotional and physical development of children [32], [33], playing is a material that develops and is rich in space for exploration [23]. Which makes fun, new knowledge, and changes in children's progress [23], thus play activities and physical activity become very important for children's basic movements [34], [35].…”
Section: Discussionmentioning
confidence: 99%